Recognition of post-mortem socio-affective paternity and its patrimonial effects on hereditary succession - Silva, Ludmila de Souza Rodrigues e (2023)
This study addresses as its theme a new form of paternity, that is, paternity arising from coexistence and affection, devoid of genetic and consanguineous ties: Socio-Affective Paternity. The objective is to analyze the patrimonial effects of recognizing post-mortem socio-affective paternity and its effects on hereditary succession. Methodologically, this is a bibliographical research of an exploratory-descriptive nature, whose approach methods are deductive and qualitative. Data collection consists of secondary sources, including legislation, doctrine and jurisprudence, preferably extracted from digital media, such as official websites, electronic article repositories and legal document consultation systems. Data analysis and processing occurred using the content analysis technique. The results demonstrate that the recognition of socio-affective paternity is possible even after death, as long as the requirements of affection and state of possession of the child are met, duly proven in a judicial process aimed at the heirs. This recognition makes it possible to include the name of the deceased in the civil registry and, consequently, generate inheritance effects, with the socio-affective child having the right to part of the inheritance that belongs to him. According to jurisprudence, the recognition of socio-affective paternity is a trend, based on constitutional precepts and provisions of the 2002 Civil Code, as there is no specific legislation. In conclusion, when socio-affective paternity is recognized, the rights of both children will be equalized: those of the heart and blood relatives.